Resistance to the sympathoexcitatory effects of insulin and leptin in late pregnant rats. (11th July 2019) - Shi, Zhigang; Hansen, Kim M.; Bullock, Kristin M.; Morofuji, Yoichi; Banks, William A.; Brooks, Virginia L.
Abstract : Key points: Pregnancy increases sympathetic nerve activity (SNA), although the mechanisms responsible for this remain unknown. We tested whether insulin or leptin, two sympathoexcitatory hormones increased during pregnancy, contribute to this. Transport of insulin across the blood–brain barrier in some brain regions, and into the cerebrospinal fluid (CSF), was increased, although brain insulin degradation was also increased. As a result, brain and CSF insulin levels were not different between pregnant and non‐pregnant rats. The sympathoexcitatory responses to insulin and leptin were abolished in pregnant rats. Blockade of arcuate nucleus insulin receptors did not lower SNA in pregnant or non‐pregnant rats. Collectively, these data suggest that pregnancy renders the brain resistant to the sympathoexcitatory effects of insulin and leptin, and that these hormones do not mediate pregnancy‐induced sympathoexcitation. Increased muscle SNA stimulates glucose uptake. Therefore, during pregnancy, peripheral insulin resistance coupled with blunted insulin‐ and leptin‐induced sympathoexcitation ensures adequate delivery of glucose to the fetus. Abstract: Pregnancy increases basal sympathetic nerve activity (SNA), although the mechanism responsible for this remains unknown. Insulin and leptin are two sympathoexcitatory hormones that increase during pregnancy, yet, pregnancy impairs central insulin‐ and leptin‐induced signalling. Therefore, to test whether insulin or leptin contribute to basal sympathoexcitation or, instead, whether pregnancy induces resistance to the sympathoexcitatory effects of insulin and leptin, we investigated α‐chloralose anaesthetized late pregnant rats, which exhibited increases in lumbar SNA (LSNA), splanchnic SNA and heart rate (HR) compared to non‐pregnant animals. In pregnant rats, transport of insulin into cerebrospinal fluid and across the blood–brain barrier in some brain regions increased, although brain insulin degradation was also increased; brain and cerebrospinal fluid insulin levels were not different between pregnant and non‐pregnant rats. Although i.c.v. insulin increased LSNA and HR and baroreflex control of LSNA and HR in non‐pregnant rats, these effects were abolished in pregnant rats. In parallel, pregnancy completely prevented the actions of leptin with respect to increasing lumbar, splanchnic and renal SNA, as well as baroreflex control of SNA. Blockade of insulin receptors (with S961) in the arcuate nucleus, the site of action of insulin, did not decrease LSNA in pregnant rats, despite blocking the effects of exogenous insulin. Thus, pregnancy is associated with central resistance to insulin and leptin, and these hormones are not responsible for the increased basal SNA of pregnancy. Because increases in LSNA to skeletal muscle stimulates glucose uptake, blunted insulin‐ and leptin‐induced sympathoexcitation reinforces systemic insulin resistance, thereby increasing the delivery of glucose to the fetus. Key points: Pregnancy increases sympathetic nerve activity (SNA), although the mechanisms responsible for this remain unknown. We tested whether insulin or leptin, two sympathoexcitatory hormones increased during pregnancy, contribute to this. Transport of insulin across the blood–brain barrier in some brain regions, and into the cerebrospinal fluid (CSF), was increased, although brain insulin degradation was also increased. As a result, brain and CSF insulin levels were not different between pregnant and non‐pregnant rats. The sympathoexcitatory responses to insulin and leptin were abolished in pregnant rats. Blockade of arcuate nucleus insulin receptors did not lower SNA in pregnant or non‐pregnant rats. Collectively, these data suggest that pregnancy renders the brain resistant to the sympathoexcitatory effects of insulin and leptin, and that these hormones do not mediate pregnancy‐induced sympathoexcitation. Increased muscle SNA stimulates glucose uptake. Therefore, during pregnancy, peripheral insulin resistance coupled with blunted insulin‐ and leptin‐induced sympathoexcitation ensures adequate delivery of glucose to the fetus.